Cannot sample enough valid points. (more)

\[\sin^{-1} \left(x + 1\right) - \sin^{-1} \left(x - 1\right)\]
\sin^{-1} \left(x + 1\right) - \sin^{-1} \left(x - 1\right)
double f(double x) {
        double r37979013 = x;
        double r37979014 = 1.0;
        double r37979015 = r37979013 + r37979014;
        double r37979016 = asin(r37979015);
        double r37979017 = r37979013 - r37979014;
        double r37979018 = asin(r37979017);
        double r37979019 = r37979016 - r37979018;
        return r37979019;
}